Architecture : the natural and the manmade - Scully, Vincent (New York : St Martins Pr, 1991)
Scully is a pioneer of 20th century architecture. This volume is the grand sum of his career. It is not only the history of great edifices, but also a book that explores the unique dialogue between human beings and their buildings and the natural world. 500 color/b&w photos.
Keywords: Nature (Aesthetics); Architecture